Immersion in social problems of civically organized populations for creating industrial design academic projects (2021)
Social projection allows the creation of meaningful educational experiences from Industrial Design academic spaces, like the subject of Social Design Workshop, where the disciplinary knowledge confluence for the creation and representation of projects that affect existing communities with a reflection on the social outlook of Colombia. The article describes the accomplishments of the pedagogical experience, with the objective of describing the applicability of the participatory and prospective design approach of the professional practice, with a high burden of social sensitivity and the recovery of material culture as fundamental elements for a relevant and contextualized social design.